2014
DOI: 10.1371/journal.pone.0097067
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Cross-Resistance to Didanosine Observed in South African Children Failing an Abacavir- or Stavudine-Based 1st-Line Regimen

Abstract: BackgroundThe knowledge-base of emerging drug resistance profiles in children exposed to abacavir-based antiretroviral regimens in South Africa is very limited. This study investigated the suitability of didanosine-based 2nd-line regimens for children in the context of antiretroviral drug resistance patterns emerging after 1st-line virologic failure.MethodsA retrospective dataset of 354 antiretroviral drug resistant genotypes from children failing either abacavir (n = 81) or stavudine (n = 273) based 1st-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, study authors were unable to assess the predicted efficacy of second-line regimens due to the lack of HIVDR data. As L74 mutations have been associated with continued AZT and tenofovir disoproxil fumarate (TDF) susceptibility 6 and even AZT hypersusceptibility of uncertain clinical significance, 10 there may be benefits to utilize AZT or TDF as second-line choices after failure on ABC-containing regimens rather than the reverse (ABC in the second line after failure on an AZT-containing regimen).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, study authors were unable to assess the predicted efficacy of second-line regimens due to the lack of HIVDR data. As L74 mutations have been associated with continued AZT and tenofovir disoproxil fumarate (TDF) susceptibility 6 and even AZT hypersusceptibility of uncertain clinical significance, 10 there may be benefits to utilize AZT or TDF as second-line choices after failure on ABC-containing regimens rather than the reverse (ABC in the second line after failure on an AZT-containing regimen).…”
Section: Discussionmentioning
confidence: 99%
“…One study in South Africa found high frequency of drug resistance mutations (DRMs) after ABC exposure in children, with virologic failure (VF) referred for resistance testing. 6 Our study describes the prevalence and characteristics associated with RT DRMs at position L74 among children found to be failing ART as part of a national survey in Kenya.…”
mentioning
confidence: 99%
“…Moreover, another study was carried out in South Africa to investigate the cross‐resistance of RPV. It is proved that RPV resistance is strongly correlated to K103N mutation . In a pharmacokinetic study of SSAT040 TMC278LA of RPV resistance, plasma sample of an unexpected seroconverter in the 300‐mg arm was collected and assessed.…”
Section: Non‐nucleoside Reverse Transcriptase Inhibitormentioning
confidence: 99%
“…Additional concerns include that ddI may not actually be virologically active in most second-line patients, due to prevalence of L74V and other known resistance mutations in NRTI-experienced patients, some having been only recently discovered. 2225 Evidence that continued use of ddI in a failing regimen may select for mutations that are associated with cross-resistance to other NRTIs, such as the Q151M complex and T69 insertion, has been described and could support discontinuation of the drug in patients currently receiving it. 2628 These considerations should be viewed in the context of resource-limited settings using a public health approach to ART regimen selection without the benefit of patient-level genotyping.…”
Section: Commentarymentioning
confidence: 99%